2016
DOI: 10.1017/s1355617715001216
|View full text |Cite
|
Sign up to set email alerts
|

Fornix Microstructure and Memory Performance Is Associated with Altered Neural Connectivity during Episodic Recognition

Abstract: Objective The purpose of this study was to assess whether age-related differences in white matter microstructure are associated with altered task-related connectivity during episodic recognition. Method Using functional magnetic resonance imaging and diffusion tensor imaging from 282 cognitively healthy middle-to-late aged adults enrolled in the Wisconsin Registry for Alzheimer's Prevention, we investigated whether fractional anisotropy (FA) within white matter regions known to decline with age was associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 91 publications
(128 reference statements)
5
14
0
Order By: Relevance
“…Our finding of a positive association between fornix FA and memory performance is in line with previous studies in both young and older adults (Rudebeck et al, 2009;Douet and Chang, 2014;Ly et al, 2016). Ly et al (2016) found that variability in fornix microstructure in middle-to-late aged adults was related to face recognition memory and partly explained preserved functional connectivity within hippocampal networks.…”
Section: Association Of Fornix White Matter Microstructure and Memorysupporting
confidence: 93%
See 1 more Smart Citation
“…Our finding of a positive association between fornix FA and memory performance is in line with previous studies in both young and older adults (Rudebeck et al, 2009;Douet and Chang, 2014;Ly et al, 2016). Ly et al (2016) found that variability in fornix microstructure in middle-to-late aged adults was related to face recognition memory and partly explained preserved functional connectivity within hippocampal networks.…”
Section: Association Of Fornix White Matter Microstructure and Memorysupporting
confidence: 93%
“…Our finding of a positive association between fornix FA and memory performance is in line with previous studies in both young and older adults (Rudebeck et al, 2009;Douet and Chang, 2014;Ly et al, 2016). Ly et al (2016) found that variability in fornix microstructure in middle-to-late aged adults was related to face recognition memory and partly explained preserved functional connectivity within hippocampal networks. A study by Metzler-Baddeley et al (2011) further suggested that specifically age-related degradation of fornix microstructure as derived from individual fiber tracking was linked to memory recall performance in strategic and visual memory tasks in older adults (Metzler-Baddeley et al, 2011).…”
Section: Association Of Fornix White Matter Microstructure and Memorysupporting
confidence: 93%
“…Clarifying the role of melatonin within hippocampus‐dependent learning and memory will foster our understanding of circadian rhythm organization in cognition. Lastly, it was shown that disturbance of the hippocampal circuity severely affects sleep and cognition in fish and in humans . In light of an increased awareness of the link between sleep‐wake disturbances in a 24‐hour society and cognitive and neurodegenerative disorders in humans, a better understanding of how the circadian clock modulates hippocampal circuity and the role of melatonin within this mechanism have great merit.…”
Section: Discussionmentioning
confidence: 99%
“…Diffusion weighted imaging data were preprocessed using a robust pipeline also used in a number of previous studies (Adluru et al, 2014; Ly et al, 2016; Merluzzi et al, 2016; Racine et al, 2017). DWI data from baseline and follow-up visits were first converted from Digital Imaging and Communication in Medicine (DICOM) format to Neuroimaging Informatics Technology Initiative (NIFTI) format and visually inspected for artifacts.…”
Section: Methodsmentioning
confidence: 99%